Effective police supervision - Miller, Larry S.; More, Harry W.; Braswell, Michael C. (Routledge, 2021)
Effective Police Supervision, Ninth edition, is a time-tested text providing complete coverage of the organizational dynamics surrounding leadership of teams in an effective police department. This revised edition provides readers with the tools to excel and advance with up-to-date and timely scholarly research and legal case law on supervision. Special attention is given to recruitment, selection, and retention of police, commonly believed to be the most challenging internal issue facing agencies today. Supervisory tactics are evaluated in terms of how they work not only in the United States but in the United Kingdom and Canada as well, and chapters are enhanced with boxed features that help the reader connect ideas with realistic situations Combining behavioral theory and updated case studies, Effective Police Supervision is the preferred textbook for college-level classes on police supervision and is an essential resource for preparation for promotional exams and career development for law enforcement officers and supervisors. Information has been included to respond to current issues facing law enforcement with COVID-19 and managing protests.